Plutarch: Lives of the noble Grecians and Romans - Plutarch, 46-120?; Clough, Arthur Hugh, 1819-1861 (Salt Lake City, UT : Project Gutenberg, 1996)
"Plutarch: Lives of the noble Grecians and Romans" by Plutarch is a series of biographies written in Greek probably at the beginning of the second century. This monumental work pairs famous Greeks with Romans of similar destiny$1 (BAlexander with Caesar, Demosthenes with Cicero$1 (Bto illuminate their moral virtues and failings. Rather than pure history, Plutarch crafted ethical portraits exploring how character shaped the lives of great men. Twenty-three paired biographies survive, alongside four singular lives, offering timeless lessons through comparison and moral examination. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Parallel_Lives
Release date is 1996-10-01
Keywords: Greece -- Biography -- Early works to 1800; Rome -- Biography -- Early works to 1800